The Media Role of Palestinian Women in Hamas: الدور الإعلامي للمرأة الفلسطينية في حركة حماس - al-Zaeem, Ibrahim Sagar; Mohd Nor, Mohd Roslan (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2021)
Islam wanted both men and women to be active in the Muslim community. Each one of them has integrity and responsibility, that must be performed, according to the legitimate limits and their potential and abilities. Based on this obvious Islamic vision, Palestinian women in Islamic Movement Resistance (Hamas) contributed to support the society in all areas of advocacy, jihad, and media field. Therefore, the aim of this study is to identify Hamas’ views on women, and to monitor the role of women in Hamas’s media institutions. The researcher relied on the descriptive approach. The study came in two chapters: Women in Hamas and the role of women in media organizations. The study concluded that Hamas’ interest in women raised from a national conviction that it can contribute to liberation and building with men. Women have contributed to strengthening the strength of the society and its cohesion against the Israeli occupation. It has also succeeded in mobilizing wide support for the Palestinian issue, and change women’s stereotype, especially through TV, which was confined to women who are non-veiled.